EFL Student Teachers’ Perception and Challenges toward Online Platforms in Language Pedagogy - Mulyadi, Dodi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research aims to investigate EFL Student teachers’ perception and challenges of performing online platforms of Interactive Multimedia on Language Teaching and Learning. This study used mixed methods, qualitative and quantitative in nature. The participants of the study were 15 learners who have involved in the learning process of Interactive Multimedia on Language Learning Class. Questionnaires and interviews were used as data collection instruments. The data were analyzed and interpreted through qualitative and quantitative procedures. The results reveal that the online platforms of interactive multimedia such as Edmodo, PlayPosit, and Duolingo, TED Videos are very helpful and beneficial in improving their pedagogical competence. However, the limited time and facilities coupled with a poor Internet connection were challenges for EFL student Teachers to carry them out in educational process. The results of this study give meaningful insights for policy makers in education such principals in relation to provide the facilities to accommodate English teachers who want to employ online platforms of interactive multimedia in English teaching and learning in the classroom.